THE AIM OF SCIENCE– KNOWLEDGE OR WISDOM - Müürsepp, Peeter (Problemos, 2013)
The typical way to express the aim of science is to connect it with knowledge pursuit. This aim has been so strongly felt that sometimes typical scientific research has been called knowledge-inquiry. There is nothing wrong with knowledge as such. Especially when we have the knowledge of the highest quality, the scientific one, in mind. Still, science today should aim higher, surpass knowledge as its final goal and reach for wisdom. This brings about the need to implement wisdom-inquiry instead of knowledge-inquiry as Nicholas Maxwell has suggested. In order to succeed, the problems of living rather than the problems of knowledge have to be brought to the foreground.Keywords: Nicholas Maxwell, knowledge-inquiry, wisdom-inquiry, Rein Vihalemm, φ-scienceMokslo tikslas – žinojimas ar išmintisPeeter Müürsepp SantraukaMokslo tikslas paprastai išreiškiamas siejant jį su žinojimo siekiu. Šis tikslas juntamas taip stipriai, jog kartais net ir tipinis mokslinis tyrimas vadinamas į pažinimą orientuotu tyrinėjimu (angl. knowledge-inquiry). Žinojimas savaime nėra blogas dalykas. Ypač kai galvoje turima aukščiausioji žinojimo kokybė – mokslinis žinojimas. Tačiau šiandieną mokslas turėtų kelti aukštesnius tikslus – peržengti žinojimą kaip galutinį tikslą ir siekti išminties. Taip atsiranda poreikis vietoje į pažinimą orientuoto tyrinėjimo vykdyti į išmintį orientuotą tyrinėjimą (angl. wisdom-inquiry), kaip siūlė Nicholas Maxwellas. Norint užtikrinti sėkmę, pirmame plane turi atsidurti ne žinojimo, bet gyvenimo problemos.Pagrindiniai žodžiai: Nicholas Maxwell, į pažinimą orientuotas tyrinėjimas, į išmintį orientuotas tyrinėjimas, Rein Vihalemm